IKONOGRAFI SEBAGAI LANGKAH KERJA KREATIF CIPTA SASTRA ANAK DARI RELIEF CANDI - Fauzi, Nanang Bustanul; Rahmawati, Femi Eka (Hasta Wiyata, 2018)
Relief as a form of local wisdom comes in one form as a tool to immerse moral values in antiquity. However, the difference is too long to make relief is no longer popular in this increasingly digital era. Therefore, effort is needed to popularize the stories in relief into children's stories so that they are more easily digested, enjoyed, and used as media of character building that has been mandated by the law.The method of reading works of art that is still rarely used to reconstruct relief stories. Relief stories are only confirmed through the search of written documents that are now increasingly rare existence. The theory in question is iconography.Through this theory, the reliefs can be read and then the reading results are combined and become a story. In the preparation of the story, this theory requires several steps of work, namely, factual description and expressional descriptions. This is understood by identifying the basic shape, the arrangement of a particular line and color, or the unique shape of a piece of bronze or a stone, a natural picture such as man, animal, plant, life-aid and identifying relationships among them as an event. Some things that have been connected are connected, then character expression is exposed through poses and or gesturenya. This is called an artistic motif.The second stage is iconography, which is the process of reading the secondary meaning of the textual aspect (visual traits / artistic motives), by looking at the relationship between the visual features of a work of art with themes and concepts based on the interpretation of imagination or images, stories and allegories or symbols). For that, it takes literary studies as supporting in the form of various theories such as anthropology, sociology, socio-culture, or lifestyle, literary works, and philosophy in the context of the work studied. A specific theme or concept is expressed by the objects of art and events in the work.Â Keyword: iconography, relief, child literature